Determinación de la actividad antioxidante de los extractos de Quishuar (buddleja incana), Aliso (alnus acuminata) y Romerillo (hypericum laricifolium) localizados en 3 zonas geográficas diferentes - Llanga Guamán, Byron Geovanny (2014)
The antioxidant activity of plants characteristic of the páramo located at altitudes close to 3000 m.a.s.l. and above 4000 m.a.s.l., such as Quishuar (Buddleja incana), Aliso (Alnus acuminata) and Romerillo (Hypericum laricifoluim) located in different geographical areas of the highlands of Ecuador was determined. The research was carried out in laboratories of the Faculty of Sciences of the Escuela Superior Politécnica de Chimborazo. The study is based on determining by means of chemical and enzymatic assays the inhibitory activity of free radicals that cause functional and structural alterations, with plant extracts with antioxidant capacity, considering that the plant species investigated are exposed to high levels of ultraviolet radiation due to the location of Ecuador. The Folin-Ciocalteau method was used to quantify phenolic compounds, the AlCl3 method to quantify flavonoids and the polyphenoloxidase enzymatic inhibition method to determine antioxidant activity. Based on the results, the highest concentration of phenolic compounds is found in the Romerillo that was collected in the Polylepis-El Arenal park of the Chimborazo snow-capped mountain at an altitude of 4342 m.a.s.l. The highest concentration of flavonoids is found in the Romerillo that was collected in the vicinity of Lagunas de Atillo in the province of Chimborazo at an altitude of 3450 m above sea level. The plant species with the best antioxidant activity corresponds to Quishuar collected in Riobamba at an altitude of 2750 m.a.s.l. in contrast to Quishuar collected at 3930 m.a.s.l. with lower antioxidant activity, showing significant differences between Quishuar from different altitudes. The Aliso and Romerillo from different altitudes do not show significant differences in antioxidant activity. It is concluded that the plant species investigated have good antioxidant activity, with values close to 50% inhibition of free radicals. It is recommended to carry out studies on Alnus acuminata, Hypericum laricifolium and Buddleja incanna applying other methods to quantify antioxidant activity.